Succinct Cancer Clinical Trial Consent Forms in Rural Patients With Cancer: A Secondary Analysis of a Randomized, Double-Blinded study - Jana Wieland MD; Daniel Satele BS; Yahya Almodallal MBBS; Paul Novotny MS; Stephanie L. Pritzl MD; Sumithra J. Mandrekar PhD; Aminah Jatoi MD (Journal of Patient Experience, 2022)
Rural patients are often underrepresented in cancer clinical trials. This is a secondary analysis of a study that tested short (2000 word) versus long (6000 word) consent forms with a focus on rurality. Among 240 patients, 89 (37%) were rural. Seventy-one (80%) rural and 117 (77%) nonrural patients signed a consent form of any length ( P  = .68). Forty-one of 47 (87%) rural patients signed a short consent form; in contrast, 30 of 42 (71%) signed a long form. These trends suggest rural patients are more likely to sign short consent forms. Further study is indicated.